Means of measurement of relative quality indicators by immittance parameter - Pokhodylo, Yevgen; Yatsuk, Vasyl; Bubela, Tetiana (Видавництво Львівської політехніки, 2005)
The paper describes the problems of implementation of the differential method of product quality assessment using the immittance method. The differential method of quality control is realized through a comparison of parameters of the immittance of the controlled and reference samples. The application of traditional meters of CLR-parameters complicates the process of the differential method implementation. Such units cannot directly measure relative quality. Virtually all models of such measuring instruments measure only the parameters of the monitored object through the input device. Thus, they are not adapted to the direct measurement of relative quality indicators. The authors propose to introduce a product pattern with the values of the code-controlled measure of admittance. These values are obtained by measuring the parameters of a standard pattern of products of a given quality level with a traditional immittance meter. The structure of the measuring instrument for the direct measurement of the relative quality index is given. The method is realized by comparing the parameters of the controlled object and the electrical standard pattern in the form of a code-controlled measure of admittance. This allows building quality control means for any nonelectrical products. Controlled products are supplied by electrical parameters of immittance with means of capacitive primary converters. Direct application of the differential method of quality assessment allows simplifying the measuring instrument as much as possible and reduce the time of product quality assessment. The proposed structure of the unit enables us to determine the deviation of the relative indicator from the value one. According to the obtained value of the indicator, products can be quickly classified by quality levels.
Keywords: Differential Method; Code-Controlled Measure of Admittance; Active Component of Admittance; Reactive Component of Admittance; Standard Sample